Exploring the relationship between mobile addiction, interpersonal relationship, and academic behavior among young adults in tertiary institutions - Chan, Yuen Fook; Narasuman, Suthagar; Abdul Aziz, Norazah; Syed Mustafa, Sharifah Muzlia; Cheong, Tau Han (Universiti Utara Malaysia Press, 2021)
Purpose – Smartphones have become part and parcel of life in the 21st century. Since there has been limited research exploring the relationship between mobile addiction, interpersonal relationship, and academic behaviour among young adults in tertiary institutions, the present study has embarked on an exploration of the relationship between these three variables in the Malaysian higher education context.